Fenomena Intergenerational Employment Profesi Transporter Sampah di Kota Yogyakarta - Bisma Jatmika Tisnasasmita (Jaanur Elbarik Indonesia, 2026)
The purpose of this research is to find out whether the profession of waste transporter in the City of Jogjakarta is inherited from parents to their children, and whether this profession provides sufficient welfare. The method used was a descriptive analysis with data collected through questionnaires answered by waste transporters in 14 ministries. The concept used to explain this phenomenon is intergenerational mobility, which is supported by path dependence theory and dual labor market theory. The results of the study show that the majority of waste transporters get this profession from generation to generation. Many transporters do not have access to formal employment and running the profession because they have no choice. Nevertheless, the majority of transporters do not consider this profession to provide long-term well-being. The role of stakeholders is very necessary so that the sustainability of waste collection services can be maintained, and this informal profession can also provide welfare. The government is expected to make provisions on sustainable service rates, and customers are expected to pay the fee according to the agreed schedule.